Desain Buku Ilustrasi Informasi Astrologi Sebagai Pseudosains - Nurrahman, Ricke Putriutami; Rochmawati, Irma (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2023)
Derived from the Greek words "Astron" meaning "star" and "Logos" meaning "science," astrology is a discipline created to explore the connection between celestial object movements and Earthly experiences. Unfortunately, this knowledge is not widely understood by the general public, primarily due to a lack of accessible information on astrology's true significance. To bridge this knowledge gap, there is a need to develop informative media that can educate people about astrology conveniently and effectively. The main media for this educational effort will be an e-book containing fundamental astrology knowledge. Additionally, to enhance the reach of the main media to the target audience, supporting media will also be designed. These supporting media will include pillows, pocket books, wall clocks, bookmarks, pencil cases, tote bags, sticker packs, keychains, mugs, and tumblers. By creating both the main and supporting media, the aim is to stimulate public interest in delving deeper into the field of astrology.